Notch signaling and natural killer cell infiltration in tumor tissues underlie medulloblastoma prognosis - Kung-Hao Liang (Nature Portfolio, 2021)
Abstract Medulloblastoma is the most common embryonic brain tumor in children. We investigated a cohort of 52 Asian medulloblastoma patients aged between 0 and 19 years old, who received surgical resections and post-resection treatments in the Taipei Medical University Hospital and the Taipei Veterans General Hospital. Genome-wide RNA sequencing was performed on fresh-frozen surgical tissues. These data were analyzed using the CIBERSORTx immune deconvolution software. Two external clinical and molecular datasets from United States (n = 62) and Canada (n = 763) were used to evaluate the transferability of the gene-signature scores across ethnic populations. The abundance of 13 genes, including DLL1, are significantly associated with overall survival (All Cox regression P < 0.001). A gene-signature score was derived from the deep transcriptome, capable of indicating patients’ subsequent tumor recurrence (Hazard Ratio [HR] 1.645, confidence interval [CI] 1.337–2.025, P < 0.001) and mortality (HR 2.720, CI 1.798–4.112, P < 0.001). After the adjustment of baseline clinical factors, the score remains indicative of recurrence-free survival (HR 1.604, CI 1.292–1.992, P < 0.001) and overall survival (HR 2.781, CI 1.762–4.390, P < 0.001). Patients stratified by this score manifest not only distinct prognosis but also different molecular characteristics: Notch signaling ligands and receptors are comparatively overexpressed in patients with poorer prognosis, while tumor infiltrating natural killer cells are more abundant in patients with better prognosis. Additionally, immunohistochemical staining showed the DLL1 protein, a major ligand in the Notch signaling pathway, and the NCAM1 protein, a representative biomarker of natural killer cells, are present in the surgical tissues of patients of four molecular subgroups, WNT, SHH, Group 3 and Group 4. NCAM1 RNA level is also positively associated with the mutation burden in tumor (P = 0.023). The gene-signature score is validated successfully in the Canadian cohort (P = 0.009) as well as its three molecular subgroups (SHH, Group 3 and Group 4; P = 0.047, 0.018 and 0.040 respectively). In conclusion, pediatric medullablastoma patients can be stratified by gene-signature scores with distinct prognosis and molecular characteristics. Ligands and receptors of the Notch signaling pathway are overexpressed in the patient stratum with poorer prognosis. Tumor infiltrating natural killer cells are more abundant in the patient stratum with better prognosis.